2003
DOI: 10.1021/ja0298500
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Confirmation of the Importance of Orientation in the Anomalous Chiral Sensitivity of Second Harmonic Generation

Abstract: Macromolecular interactions were demonstrated to yield large chiroptical effects in second harmonic generation measurements of ultrathin surface films. Second harmonic generation (SHG) has recently shown to be several orders of magnitude more sensitive to chirality in oriented systems than common linear methods, including absorbance circular dichroism (CD) and optical rotary dispersion (ORD). Numerous mechanisms have been developed to explain this anomalous sensitivity, with a general emphasis on understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 58 publications
6
89
0
Order By: Relevance
“…According to the peak assignments of secondary structures of proteins, the peaks at 1,630 and 1,690 cm Ϫ1 should be contributed from ␤-sheet structures (66 -69). We believe that this characteristic must be due to the fact that ␤-sheet structures can more easily have ordered twist angles at the interface, thereby generating strong chiral signals for some vibrational modes, as suggested by Simpson and coworkers (35,36). Our work here clearly indicates that the chiral SFG spectra should provide further structural information about interfacial fibrinogen molecules.…”
Section: Chiral Sfg Vibrational Spectra Of Adsorbed Fibrinogen Obtainsupporting
confidence: 73%
See 1 more Smart Citation
“…According to the peak assignments of secondary structures of proteins, the peaks at 1,630 and 1,690 cm Ϫ1 should be contributed from ␤-sheet structures (66 -69). We believe that this characteristic must be due to the fact that ␤-sheet structures can more easily have ordered twist angles at the interface, thereby generating strong chiral signals for some vibrational modes, as suggested by Simpson and coworkers (35,36). Our work here clearly indicates that the chiral SFG spectra should provide further structural information about interfacial fibrinogen molecules.…”
Section: Chiral Sfg Vibrational Spectra Of Adsorbed Fibrinogen Obtainsupporting
confidence: 73%
“…Electronic resonance enhancement is used to detect chiral SFG vibrational spectra generated from the molecular chirality, because under electronic resonance the asymmetric Raman tensor components will be greatly enhanced by the electronicvibrational coupling (18). Strong SHG and SFG signals can be observed from chiral molecules; however, Simpson and coworkers (33)(34)(35)(36)(37) demonstrated by using SHG that achiral molecules adsorbed on a surface or interface may generate detectable nonlinear optical chiral signals. They concluded that macromolecular orientational effects can dominate the chiroptical responses of uniaxial systems.…”
mentioning
confidence: 99%
“…[7,[10][11][12][13][14][15] More recently, theoretical and experimental evidence suggests that macromolecular orientational effects alone can dominate the chiroptical responses of uniaxial systems without the need for multiple coupled oscillators or even chiral chromophores at all (Figure 1 c). [7,8,[42][43][44][45][46] [a] Prof. G. J. Simpson Department of Chemistry Purdue University, West Lafayette IN 47907 Fax:(+ 1) 765-494-0239 E-mail: gsimpson@purdue.edu Figure 1.…”
Section: Chiroptical Effects In Shg and Sfg Measurements Of Oriented mentioning
confidence: 99%
“…The generation of macromolecular chiroptical activity in chiral assemblies of achiral chromophores (referred to as structural rotary power) is reasonably well-understood in absorbance measurements of chiral media, [71,72] but has only relatively recently been applied to the interpretation of chiroptical effects in SHG and SFG of oriented systems. [7,8,42,43,45,46,62] Although predictions of possible chiroptical effects in SHG from oriented assemblies of planar chromophores with C 2v symmetry were reported as early as 1987, [73] most of the work in characterizing the role of molecular orientation in driving chiroptical phenomena in SHG and SFG of uniaxial films and interfaces has been performed within the last few years. [7,8,42,43,45,46,62] In both planar chromophores with C 2v symmetry and in "two-state" chromophores, in which the nonlinear optical properties of the chromophore are reasonably well-described by considering interactions between the ground state and a single excited state, only four elements within the molecular tensor are significant in electronically resonant SHG and SFG: b zzz , b zxx , b xzx , and b xxz .…”
Section: Structural Chirality In Films Containing Achiral Chromophoresmentioning
confidence: 99%
See 1 more Smart Citation